Maritime Criminal Justice Transformation: A Responsive and Restorative Approach to Law Enforcement in Indonesian Waters - Napitupulu, Amin Pardomuan; Yusuf Hasibuan, Fauzie; Akkapin, Supaphorn (CV. Era Digital Nusantara, 2025)
As the world's largest archipelagic country, Indonesia faces serious challenges in enforcing criminal laws in its vast maritime territory. The current legal framework is still dominated by a fragmented, sectoral, and repressive approach that fails to address the structural and contextual nature of maritime crimes such as illegal fishing, smuggling, and marine environmental degradation. This article offers a transformative approach to Indonesia’s maritime criminal justice system by integrating responsive law theory and transformative justice into a contextual and participatory model. Through a combined normative and empirical approach, including regulatory analysis and field studies in strategic maritime areas, this study finds that the retributive criminal justice system is ineffective and lacks legitimacy, especially in cases involving marginalized coastal communities. As an alternative, this article proposes a tripartite model based on community penal mediation, digital-based inter-institutional coordination, and the harmonization of substantive legal norms within the framework of the national Criminal Code. This model aims to build a criminal justice system that is more just, participatory, and sensitive to ecological considerations.